SOCIAL ORDER DIMENSION IN SUPERSTITION PREGNANT WOMAN FOR KUBUANG TIGO BALEH SOCIETY - Ulya, Ridha Hasnul (Universitas PGRI Sumatera Barat, 2022)
This research is motivated by problems and phenomena regarding the behavior and ethics of pregnant women in the Kubuang Tigo Baleh community. This study aims to describe the patterns, functions, and ethical values in the superstition of pregnant women in the Kubuang Tigo Baleh community. This research is a type of qualitative research, data collection techniques carried out by observation and unstructured interviews with informants. This research data analysis technique uses three stages, namely data reduction, data display, and conclusions. The results of this study indicate that: the superstition of pregnant women Kubuang Tigo Baleh community is a means of educating behavior, the superstition of pregnant women Kubuang Tigo Baleh community is associative, and the superstition of pregnant women Kubuang Tigo Baleh community is always created through the context of events. Therefore, it can be concluded that the superstition of pregnant women in Kubuang Tigo Baleh community is an expression of local wisdom in directing behavior, actions, and ethics.